1979
DOI: 10.1093/ajcn/32.8.1686
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ascorbic acid and flavonoids on the occurrence of symptoms normally associated with the common cold

Abstract: A controlled study was made of the effects of natural orange juice, synthetic orange juice, and placebo in the prevention of the common cold; both natural and synthetic orange juices contained 80 mg of ascorbic acid daily. Three-hundred sixty-two healthy normal young adult volunteers, ages 17 to 25 years, were studied for 72 days with 97% of participants completing the trial. There was a 14 to 21% reduction in total symptoms due to the common cold in the supplemented groups that was statistically significant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…4. There is only a slight difference between the two male groups of Baird et al (1979) who were administered 80 mg vitamin C/d, and the difference is not in favour of orange juice. The number of cold episodes was ninety-one and ninety-three among the male subjects administered 80 mg/d in orange juice (n 62) and in synthetic drink (n 71) respectively, yielding RR = 0•89 (95 % CI: 0•67, 1•19) in favour of the synthetic drink.…”
Section: Reply By Hemilämentioning
confidence: 83%
See 3 more Smart Citations
“…4. There is only a slight difference between the two male groups of Baird et al (1979) who were administered 80 mg vitamin C/d, and the difference is not in favour of orange juice. The number of cold episodes was ninety-one and ninety-three among the male subjects administered 80 mg/d in orange juice (n 62) and in synthetic drink (n 71) respectively, yielding RR = 0•89 (95 % CI: 0•67, 1•19) in favour of the synthetic drink.…”
Section: Reply By Hemilämentioning
confidence: 83%
“…Fourth, the intervention group in the study by Baird et al (1979) was a mixture of two sub-groups, one of which received a synthetic drink with 80 mg vitamin C, and the other received natural orange juice containing 80 mg vitamin C plus flavonoids etc. By combining these two sub-groups in his analysis, Hemilä fails to recognize the possible nonvitamin C-related effects of orange juice.…”
Section: Nutrition Discussion Forummentioning
confidence: 99%
See 2 more Smart Citations
“…Six, large randomized trials of normally nourished subjects in Western countries, whose supplementation period ranged from 2 to 9 months, revealed no effect of vitamin C on common cold incidence (Anderson et al, 1972;Karlowski et al, 1975;Elwood et al, 1976;Ludvigsson et al, 1977;Pitt and Costrini, 1979;Briggs, 1984). However, studies of specific groups, such as subjects under heavy acute physical stress (Hemila, 1996) or British males with extremely low levels of vitamin C intake (Glazebrook and Thomson, 1942;Charleston and Clegg, 1972;Clegg and Macdonald, 1975;Baird et al, 1979), revealed significant reduction in common cold incidence with vitamin C supplementation. In addition, studies have consistently found reduced duration or severity of the common cold with vitamin C supplementation (Hemila and Douglas, 1999).…”
Section: Introductionmentioning
confidence: 99%